De novo developed microsatellite markers in gill parasites of the genus Dactylogyrus (Monogenea): Revealing the phylogeographic pattern of population structure in the generalist parasite Dactylogyrus vistulae - Benovics, Michal; Gettová, Lenka; Šimková, Andrea (Ecology and evolution, 2021)
Approaches using microsatellite markers are considered the gold standard for modern population genetic studies. However, although they have found application in research into various platyhelminth taxa, they remained substantially underutilized in the study of monogeneans. In the present study, a newly developed set of 24 microsatellite markers was used to investigate the genetic diversity of the generalist monogenean species Dactylogyrus vistulae. The analyzed parasite specimens were collected from 13 cyprinoid species from 11 sites in the Apennine and Balkan peninsulas. A total of 159 specimens were genotyped at each of the loci and the number of alleles per locus ranged from 2 to 16, with a mean number of 6.958 alleles per locus. Exceptionally high genetic diversity was observed among D. vistulae individuals in the southern Balkans (mean N A per locus = 3.917), suggesting that generalist D. vistulae expanded from the south to the north in the Balkans and later into central Europe. The initial clustering analysis divided all investigated specimens into three major clusters; however, the results of the subsequent analyses revealed the existence of various subpopulations, suggesting that the population structure of D. vistulae is associated with the diversification of their cyprinoid hosts. In addition, the partition of the parasite population was observed in regions of the sympatric occurrence of two host species, indicating that these hosts may represent a barrier for gene flow, even for generalist parasite species.
Keywords: host‐specific parasites; Cyprinoidei; polymorphic markers; population genetics; historical dispersion